Persepsi Masyarakat Badui terhadap Pandemi Covid-19 - Andriani, Yuyun; Wilantara, Made; Elizabeth, Novianty (LUGAS Jurnal Komunikasi, 2023)
Communication is the main factor influencing the success of mitigating the Covid-19 pandemic in remote Baduy tribe areas. Traditional lifestyle practices in daily activities reflect the life of the Baduy tribe who are always guided by the tribe's cultural norms (pikukuh). It was found that there were no positive cases of Covid-19 in the Baduy tribe community. The aim of the study was to find out the communication strategy that the Puun (the highest cultural leader in Baduy Tribe) and the Jaro Pamarentah (Head of the village) emphasized in order to shape the social perceptions of the Baduy Tribe to avoid transmission of Covid-19. The research was conducted using qualitative methods with constructivism paradigm. This research shows that the perception of the Baduy Tribe is formed through the central role of the Puun and the Jaro Pamarentah through a cultural approach by giving an appeal that the Covid-19 outbreak is very dangerous based on the reality that is happening to the surrounding community. By implementing pikukuh in carrying out their daily life it is suggested that it protected them from the threat of the Covid-19 outbreak.